2001
DOI: 10.1051/0004-6361:20010750
|View full text |Cite
|
Sign up to set email alerts
|

ROSAT-HRIobservations of six southern galaxy pairs

Abstract: Abstract. We present the detailed analysis of the X-ray data for 6 pairs, isolated or in poor groups, observed at high resolution with the ROSAT HRI . In all cases, the stronger X-ray source is associated with the brighter early-type member and is extended. The extent varies from galactic to group scale, from 3 (RR 210b) to 182 kpc( RR 22a). The fainter members are detected only in two pairs, RR 210 and RR 259. Except for one case, no significant substructures have been detected in the X-ray maps, possibly als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…In contrast to their similar optical characteristics, their X-ray properties (see also Trinchieri & Rampazzo 2001) indicate that their X-ray luminosities, L X /L B ratios and morphologies are very different, which implies that they have different origins and/or represent different evolutionary stages of the systems. X-ray emission in RR 143 and RR 242 is centred on the elliptical but is much more extended than the optical light.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to their similar optical characteristics, their X-ray properties (see also Trinchieri & Rampazzo 2001) indicate that their X-ray luminosities, L X /L B ratios and morphologies are very different, which implies that they have different origins and/or represent different evolutionary stages of the systems. X-ray emission in RR 143 and RR 242 is centred on the elliptical but is much more extended than the optical light.…”
Section: Introductionmentioning
confidence: 99%
“…We have presently only very limited information on the X-ray properties of mixed pairs Henriksen & Cousineau 1999;Trinchieri & Rampazzo 2001) with detected ETG members showing X-ray luminosities and L X /L B ratios that span the full range observed for early-type galaxies in general. A group-like extension has been detected in some pairs but there is no evidence that pair membership affects the global X-ray properties of galaxies (Trinchieri & Rampazzo 2001). Detection of diffuse X-ray emission in some pairs might offer the best means to identify systems that are actively involved in a hierarchical merging process.…”
Section: Introductionmentioning
confidence: 99%
“…In the above context we present: 1) new XMM-Newton observations of two E+S pairs (RR 143 and RR 242) both of which show diffuse emission (plus pairs RR 210 and RR 216 previously observed with ROSAT (Trinchieri & Rampazzo 2001)) and 2) results of an optical photometric search for tidal features/optical diffuse light and a study of candidate faint galaxy populations that might be associated with the pairs. Groups studied by Zabludoff & Mulchaey (1998) revealed a significantly higher number of faint galaxies (≈50 members down to magnitudes as faint as M B ≈ -14 +5log 10 h 100 ) in groups with a hot IGM compared to groups without this component.…”
Section: Introductionmentioning
confidence: 99%
“…Recent X‐ray studies have shown that a significant amount of a diffuse emission could be present in galaxy groups (Mulchaey et al 1993, 1996, 2003; Ponman et al 1996; Mulchaey 2000; Gomez et al 2003, see, for example,) and even in physical pairs composed of an elliptical and a spiral member (Rampazzo et al 1998; Henriksen & Cousineau 1999; Trinchieri & Rampazzo 2001). However, it is still unclear whether massive groups, whose dominant galaxy is a spiral, do exist (Mulchaey 2000; Kelm & Focardi 2004).…”
Section: Introductionmentioning
confidence: 99%